2016
DOI: 10.1039/c6gc00724d
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, mechanistic and kinetic studies on the organo-nanocatalyzed synthesis of oxygen and nitrogen containing spiro compounds under ultrasonic conditions

Abstract: Vitamin B1 functionalised nano-ferrites: an organo-nanocatalyst for the synthesis of various spiro derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The challenge here was that vitamin B1 is too water soluble, which compromises its reusability, which was solved by its immobilization onto magnetic nanoparticles, facilitating the work-up and the catalyst recovery by using an external magnet. They also used ultrasound irradiation to increase the rate of the reaction and observed that it could be conducted in fifteen minutes, while six hours were required when using conventional heating [48,49]. The high activity of the catalyst arises from its ability of acting as hydrogen bond donor through its hydroxyl groups and the fact that it carries the nucleophile that promotes the epoxide ring opening, the iodide anion.…”
Section: Immobilized Organocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge here was that vitamin B1 is too water soluble, which compromises its reusability, which was solved by its immobilization onto magnetic nanoparticles, facilitating the work-up and the catalyst recovery by using an external magnet. They also used ultrasound irradiation to increase the rate of the reaction and observed that it could be conducted in fifteen minutes, while six hours were required when using conventional heating [48,49]. The high activity of the catalyst arises from its ability of acting as hydrogen bond donor through its hydroxyl groups and the fact that it carries the nucleophile that promotes the epoxide ring opening, the iodide anion.…”
Section: Immobilized Organocatalystsmentioning
confidence: 99%
“…Another important synthetic challenge is the construction of non-aromatic polycyclic skeletons due to their presence in bioative molecules. In this sense, Greck et al reported a one-pot reaction for the direct conversion of hydroquinone derivatives (49) into enantioenriched tricyclic skeletons. The reaction takes place through an oxidative dearomatization and is catalyzed by amine 50 in a Diels-Alder/Michael cascade process (Scheme 11) [19].…”
mentioning
confidence: 99%
“…Due to their wide range of biological properties, the development of simple methods for efficient preparation of spiro[4 H ‐pyran‐3,3′‐oxindoles] is an important synthetic goal for the chemical community. Many reports have been disclosed for the synthesis of these compounds, which often involved an one‐pot, three‐component condensation of isatins with malononitrile and enol derivatives . Despite great progress, these synthetic methods still suffer a common major drawbacks, the use of a large amount of catalyst, which is incompatible with industrial demands for cost‐efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, very recently, Nongkhlaw et al . reported for the development of a organo‐nanocatalysts where a thiamine hydrochloride as an eco‐friendly, inexpensive, naturally occurring, water soluble organocatalysis was supported onto Fe 3 O 4 @SiO 2 and studied its catalytic behavior in nitrogen containing spiro heterocycles synthesis . However, the use of thiamine tagged Ni 2+ immobilized on the small size magnetic Fe 3 O 4 nanoparticle as a support remains unexplored.…”
Section: Introductionmentioning
confidence: 99%